ChemInform Abstract: A Cascade Synthesis of Aminohydantoins Using in situ‐Generated N‐Substituted Isocyanates. Issue 28 (July 2015) - Vincent‐Rocan, Jean‐Francois; Clavette, Christian; Leckett, Kyle; Beauchemin, Andre M.
Abstract Simple hydrazides and hydrazones are used as precursors of the required N‐substituted isocyanates.